Protein targeting by tyrosine- and di-leucine-based signals: evidence for distinct saturable components. - Michael S. Marks; Lorande Loss Woodruff; Hiroshi Ohno; Juan S. Bonifacino (1996)
Targeting of transmembrane proteins to lysosomes, endosomal compartments, or the trans-Golgi network is largely dependent upon cytoplasmically exposed sorting signals. Among the most widely used signals are those that conform to the tyrosine-based motif, YXXO (where Y is tyrosine, X is any amino acid, and O is an amino acid with a bulky hydrophobic group), and to the di-leucine (or LL) motif. Signals conforming to both motifs have been implicated in protein localization to similar post-Golgi compartments. We have exploited the saturability of sorting to ask whether different YXXO or LL signals use shared components of the targeting machinery. Chimeric proteins containing various cytoplasmic domains and/or targeting signals were overexpressed in HeLa cells by transient transfection. Endogenous transferrin receptor and lysosomal proteins accumulated at the cell surface upon overexpression of chimeric proteins containing functional YXXO targeting signals, regardless of the compartmental destination imparted by the signal. Furthermore, overexpression of these chimeric proteins compromised YXXO-mediated endocytosis and lysosomal delivery. These activities were ablated by mutating the signals or by appending sequences that conformed to the YXXO motif but lacked targeting activity. Interestingly, overexpression of chimeric proteins containing cytoplasmic LL signals failed to induce surface displacement of endogenous YXXO-containing proteins, but did displace other proteins containing LL motifs. Our data demonstrate that: (a) Protein targeting and internalization mediated by either YXXO or LL motifs are saturable processes; (b) common saturable components are used in YXXO-mediated protein internalization and targeting to different post-Golgi compartments; and (c) YXXO- and LL-mediated targeting mechanisms use distinct saturable components.